2008
DOI: 10.1128/cvi.00397-07
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cellular Immune Responses with Protection against Culture-Confirmed Influenza Virus in Young Children

Abstract: The highly sensitive gamma interferon (IFN-␥) enzyme-linked immunosorbent spot (ELISPOT) assay permits the investigation of the role of cell-mediated immunity (CMI) in the protection of young children against influenza. Preliminary studies of young children confirmed that the IFN-␥ ELISPOT assay was a more sensitive measure of influenza memory immune responses than serum antibody and that among seronegative children aged 6 to <36 months, an intranasal dose of 10 7 fluorescent focus units (FFU) of a live attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(153 citation statements)
references
References 69 publications
4
147
2
Order By: Relevance
“…Recently, it was shown that the numbers of spot-forming cells correlate with clinical protection from culture-confirmed influenza in young children (21). These numbers may vary depending on the antigen type and influenza strain, because median numbers in our assays were higher than those in assays in which hemagglutinin or vaccine components were used (9,(21)(22)(23), and as in the present study, A/H3N2-specific cell-mediated responses were lower than A/H1N1-specific responses. WIV contains core antigens in addition to surface antigens.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, it was shown that the numbers of spot-forming cells correlate with clinical protection from culture-confirmed influenza in young children (21). These numbers may vary depending on the antigen type and influenza strain, because median numbers in our assays were higher than those in assays in which hemagglutinin or vaccine components were used (9,(21)(22)(23), and as in the present study, A/H3N2-specific cell-mediated responses were lower than A/H1N1-specific responses. WIV contains core antigens in addition to surface antigens.…”
Section: Discussionsupporting
confidence: 53%
“…Multiple prospective, randomized, controlled studies have described the efficacy of live attenuated influenza vaccine (LAIV) in children and adolescents compared with placebo and with trivalent inactivated influenza vaccine (TIV) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 . LAIV provided levels of efficacy against influenza illness that, in the three comparative studies conducted, were significantly higher than those provided by TIV 1 , 3 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…S2). Because unadjuvanted s-TIV is generally not effective in inducing influenza-specific CD8 + T cells (25)(26)(27), not surprisingly, mice that received s-TIV did not have a significant number of influenza-specific CD8 + T cells in the lungs. On the other hand, in mice infected with s-WT virus, ∼10% of the pulmonary CD8 + T cells on day 8 after primary infection were specific for NP 147 , a conserved cytotoxic T cell (CTL) epitope in the nucleoprotein.…”
Section: Elisa Antibodymentioning
confidence: 99%